(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2019)
Twenty fresh clover honey, ten beeswax and ten bee bread samples represented contaminated and non-contaminated areas were collected directly from the apiaries during 2015 .The aim of this study was to evaluate the presence of toxic metals ( Lead (Pb), Cadmium (Cd), Iron (Fe), Copper (Cu) and Zinc (Zn)) in honey, beeswax and bee bread stored inside honey bee colonies. The highest lead contents (0.5488 mg/kg) was estimated in honey samples collected from industrialized area The lowest Pb content were estimated in honey samples collected from rural area (0.5096 mg/kg). The lowest Cd concentration (0.0961 mg/kg). However, the highest content of Cd (0.1042 mg/kg) was recorded in honey samples collected from urbanized areas. High concentration of (Cu) was estimated in honey samples collected from apiaries located in industrialized area (0.0757 mg/kg) while the lowest were recorded in rural area (0.0432 mg/kg) . Zn occurred in low concentration in honey samples The highest value was recorded in honey samples from rural area (0.241) mg/kg and the lowest in honey samples from apiaries located in Reclaimed soils (0.185) mg/kg. Heavy metal concentrations of Pb, Cd, Fe, Cu and Zn in beeswax samples collected from contaminated and non-contaminated areas were 1.388, 0.194, 16.696, 0.619 and 4.606 mg/kg. While the averages of heavy metal concentrations in non contaminated area decreased to 1.175; 0.160; 15.466; 0.391 and 2.520 mg/kg, respectively. Contamination in bee bread samples showed that lead concentration (1.094 mg/kg to 1.338 mg/kg) was detected in bee bread samples collected from honey bee colonies located in non-contaminated areas and samples collected from( industrialized and urban areas).